Bone marrow transcriptome and epigenome profiles of equine common variable immunodeficiency patients unveil block of B lymphocyte differentiation - Tallmadge, Rebecca L. (Clin Immunol, 2015)
Common variable immunodeficiency (CVID) is a late-onset humoral deficiency characterized by B lymphocyte dysfunction or loss, decreased immunoglobulin production, and recurrent bacterial infections. CVID is the most frequent human primary immunodeficiency but still presents challenges in the understanding of its etiology and treatment. CVID in equine patients manifests with a natural impairment of B lymphocyte differentiation, and is a unique model to identify genetic and epigenetic mechanisms of disease. Bone marrow transcriptome analyses revealed decreased expression of genes indicative of the pro-B cell differentiation stage, importantly PAX5 (p≤0.023). We hypothesized that aberrant epigenetic regulation caused PAX5 gene silencing, resulting in the late-onset and non-familial manifestation of CVID. A significant increase in PAX5 enhancer region methylation was identified in equine CVID patients by genome-wide reduced-representation bisulfite sequencing and bisulfite PCR sequencing (p=0.000). Thus, we demonstrate that integrating transcriptomics and epigenetics in CVID enlightens potential mechanisms of dysfunctional B lymphopoiesis or function.